Overview of Survey Results of the Healthy Indonesia Program with a Family Approach In the area of Penggaron Lor, Semarang - Lahdji, Aisyah (Qanun Medika - Medical Journal Faculty of Medicine Muhammadiyah Surabaya, 2019)
ABSTRACT Health Development Index (HDI) greatly influences health status. Efforts to achieve healthy development are carried out by implementing Healthy Indonesia Program with A Family Approach (Program Indonesia Sehat dengan Pendekatan Keluarga or PIS-PK). The implementation of the PIS-PK was established with 12 main indicators, which aimed at improving the quality of life. The purpose of this study was to find out family health problems by identifying problems and analyzing the causes of health problems in the working area of Bangetayu Public Health Care (RW I, RT 5, 6, 7, 8, and 9) in Penggaron Lor, Semarang. This research is observational descriptive with a cross-sectional approach through interviews and filling in family health profile data in RW I, RT 5, 6, 7, 8, and 9. The problem obtained from the interview was an analysis of the causes of the problem using the L-Green Theory. The survey results showed that the health indexes with healthy categories consisted of 29 families, pre-healthy 113 families, and unhealthy 14 families, with three lowest indicators of PIS-PK are hypertension without regular medication (22%), no family members smoke (39%) and families join the family planning program (37%). In conclusion, there are three problems from 12 healthy family indicators occur in Penggaron Lor, which are families who participate in the family planning program, hypertensive patients who take regular medication, and no family members who are smokers. Keywords : PIS-PK, healthy family, Penggaron Lor Correspondence : lahdjiaa@yahoo.com ABSTRAK Derajat Kesehatan merupakan salah satu unsur penting dalam meningkatkan Indeks Pembangunan Manusia (IPM). Upaya mencapai pembangunan kesehatan dilakukan dengan melaksanakan Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK). Penyelenggaraan PIS-PK ditetapkan dengan adanya 12 indikator utama yang bertujuan untuk meningkatkan kualitas hidup masyarakat Indonesia, dengan mengutamakan pelayanan promotif dan preventif. Tujuan penelitian ini adalah untuk mengetahui masalah kesehatan keluarga dengan mengidentifikasi masalah dan menganalisis penyebab masalah kesehatan di wilayah kerja Puskesmas Bangetayu, RW 1 (RT 5, 6, 7, 8, dan 9), Kelurahan Penggaron Lor, Semarang. Penelitian ini termasuk deskriptif observasional dengan pendekatan cross sectional melalui wawancara dan pengisian data profil kesehatan keluarga di wilayah RW I (RT 5, 6, 7, 8, dan 9). Penyebab pada masalah yang didapatkan dari wawancara dianalisis menggunakan Teori L-Green. Hasil survei menunjukkan warga wilayah RW I (RT 5, 6, 7, 8, dan 9), Kelurahan Penggaron Lor, Semarang berindeks kesehatan dengan kategori sehat sebanyak 29 Kepala Keluarga (KK), pra sehat 113 KK, dan tidak sehat 14 KK, dengan 3 indikator terendah PIS-PK yaitu hipertensi yang tidak melakukan pengobatan secara teratur (22 %), anggota keluarga tidak ada yang merokok (39 %) dan keluarga mengikuti program KB (37%). Kesimpulan penelitian ini adalah terdapat 3 masalah dari 12 indikator keluarga sehat yang terjadi di Kelurahan Penggaron Lor yaitu keluarga mengikuti program KB, penderita hipertensi yang berobat teratur, dan tidak ada anggota keluarga yang merokok. Kata Kunci : PIS-PK, Keluarga Sehat, Penggaron Lor Korespondensi : lahdjiaa@yahoo.com